Are Farmers Willing to Pay for Centralized Mode Provision of Rural Domestic Sewage Treatment? A Large-Scale Assessment in North China - Jiao, Jian; Yang, Zihong; Zhang, Yang; Shi, Boyang; Dogot, Thomas; Yin, Changbin (Frontiers in Environmental Science, 2022)
Exploring the farmer’s participation mechanism and payment mechanism of centralized mode provision (CMP) may effectively resolve the predicament of insufficient CMP for improving rural living environment and achieving sustainable development goals (SDGs). This study adopted the contingent valuation method as well as face-to-face interview questionnaires to assess rural residents' provision mode preferences, willingness to participate (WTPP) and willingness to pay (WTP) for CMP of RDST in China. Based on 761 samples collected in Shandong, Jilin and Gansu provinces of China, we applied econometric models to estimate farmers' WTPP and WTP for CMP of RDST and explore the potential influencing factors, respectively. Results show that: (1) 81.87% of farmers would be willing to contribute to CMP of RDST; (2) farmers' perceptions of the necessity of RDST, pollution of rural domestic sewage, and government propaganda significantly and positively affect their WTP; (3) the expected WTP for CMP of RDST with the total respondents and the respondents with positive WTPP were estimated to be 47.46 CNY/year and 63.13 CNY/year (for a total of 20 years), accounting for 16.28% and 21.65% of construction costs, respectively. Based on these outcomes, it could be further estimated that the aggregate value was between 1.1 billion CNY/year and 1.2 billion CNY/year which implying that farmers' WTP may be a potentially non-negligible funding source for the CMP of RDST. The enhancement of environmental awareness of farmers and strengthening of propaganda should be the next priority of the Chinese government. Priority should also be assigned to villages closer to towns when the government formulates relevant strategies and policies. The results of this study provide references for policy formulation related to broadening the funding sources in RDST and exploring farmer payment mechanisms and implications for other developing countries.